A free-standing 3D porous all-ceramic cathode for high capacity, long cycle life Li–O2 batteries. Issue 95 (16th November 2021) - Wang, Yuxin; Han, Da; Kang, Feiyu; Zhai, Dengyun
Abstract : A porous all-ceramic RuO2 @La0.7 Ca0.3 CuO3 cathode for Li–O2 batteries achieved a high capacity of 21 518 mA h g −1 and a high reversible cycling stability. Abstract : The all-ceramic RuO2 @La0.7 Ca0.3 CuO3 membrane cathode contributes to an ultra-high capacity of 21 518 mA h g −1 over 110 cycles in Li–O2 batteries. A simple infiltration technique is effective for obtaining a highly active supported RuO2 catalyst, and a solvent with a high donor number should be preferentially chosen because it contributes to a much higher capacity.